Challenges to learning and leading the digital workplace. Issue 3 (2nd September 2022) - Vallo Hult, Helena; Byström, Katriina
ABSTRACT: Digitalisation does not only transform material constructions of workplaces and work but also social constructions for employees' interaction and learning at work. In this paper, we explore emerging challenges related to the digitalisation of workplaces aiming for an understanding of the changing prerequisites for working and competence. Our findings from a small qualitative exploratory study illustrate the complexity of the development of workplaces, characterised by strong but diffuse relationships between people, technology, and work practices. We argue that in the development of digital workplaces, a sole focus on information systems as new technology, along with training and education of their functionality is insufficient. First, the demand for new competencies in the workplace calls for understanding learning practices in everyday digital work. Second, leading the transition towards a digital workplace requires learning new leadership practices. Thus, an understanding of work rather than systems ought to be central in the future digitalisation of work, in which the systems are one part of development, not the development.